Polymorphism in the Bordetella pertussis Virulence Factors P.69/Pertactin and Pertussis Toxin in The Netherlands: Temporal Trends and Evidence for Vaccine-Driven Evolution - Mooi, Frits R. (American Society for Microbiology, 1998)
The Bordetella pertussis proteins P.69 (also designated pertactin) and pertussis toxin are important virulence factors and have been shown to confer protective immunity in animals and humans. Both proteins are used in the new generation of acellular pertussis vaccines (ACVs), and it is therefore important to study the degree of antigenic variation in these proteins. Sequence analysis of the genes for P.69 and the pertussis toxin S1 subunit, using strains collected from Dutch patients in the period 1949 to 1996, revealed three P.69 and three S1 variants which show differences in amino acid sequence. Polymorphism in P.69 was confined to a region comprised of repeats and located proximal to the RGD motif involved in adherence to host tissues. Variation in S1 was observed in two regions previously identified as T-cell epitopes. P.69 and S1 variants, identical to those included in the Dutch whole-cell pertussis vaccine (WCV), were found in 100% of the strains from the 1950s, the period when the WCV was introduced in The Netherlands. However, nonvaccine types of P.69 and S1 gradually replaced the vaccine types in later years and were found in ∼90% strains from 1990 to 1996. These results suggest that vaccination has selected for strains which are antigenically distinct from vaccine strains. Analysis of strains from vaccinated and nonvaccinated individuals indicated that the WCV protects better against strains with the vaccine type P.69 than against strains with non-vaccine types (P = 0.024). ACVs contain P.69 and S1 types which are found in only 10% of recent Dutch B. pertussis isolates, implying that they do not have an optimal composition. Our findings cast a new light on the reemergence of pertussis in highly vaccinated populations and may have major implications for the long-term efficacy of both WCVs and ACVs.